Ferroptosis in the tumor microenvironment: mechanisms, advances, and therapeutic perspectives - Gao, Weijuan; Tan, Jiani; Yu, Chengtao (Frontiers in Oncology, 2025)
Ferroptosis is a regulated, non-apoptotic form of cell death marked by the accumulation of iron-dependent lipid peroxides. This process causes rapid rupture of the plasma membrane and the release of intracellular contents. Ferroptosis acts as an intrinsic tumor-suppressive mechanism. It plays a crucial role in tumor progression, metastasis, and resistance to standard therapies, including chemotherapy and radiotherapy. Its unique molecular mechanisms confer significant therapeutic potential. In recent years, multiple experimental therapies aiming to induce ferroptosis have been developed for cancer treatment. Although these therapies show promise in controlling tumor growth, their effects on the tumor microenvironment (TME) require further investigation. Recent studies indicate that distinct cell populations within the TME have different sensitivities to ferroptosis. This variability may lead to unintended effects, such as damage to normal cells or increased inflammation, resulting in toxicity. Cells in the TME can either undergo ferroptosis or modulate its regulation through intercellular signaling and interactions. Notably, ferroptosis-related interactions between tumor cells and other components of the TME, such as immune cells, stromal cells, and endothelial cells, are central to TME remodeling. This mini-review summarizes recent advances in ferroptosis mechanisms and highlights the dynamic interplay between ferroptosis and the TME. It also discusses the prospects and challenges of ferroptosis-based cancer therapies.